Branch gall of mango (Oligotrophus mangiferae Keiffer) – its bioecology and management (The Journal of Plant Protection Sciences, 2022)
The branch gall, Oligotrophus mangiferae Keiffer has recently appeared in serious proportion in the major mango  growing districts of West Bengal, India. The present study had been taken up regarding the biology, population  dynamics and management of this pest. Branch gall is a univoltine species. Emergence of adults from gall could be  found from 2nd week of February, which continued up to 2nd week of March. Incubation, larval and pupal period  lasted for 3-5 days, 315 days and 30-45 days, respectively. Eggs were laid singly throughout the young vegetative  shoots by puncturing the tissue. A full grown larva was yellow in colour with a clear dark brown constriction on  head. Initially the pupa was creamy white in colour which gradually turned light yellow and finally blackish.  Adults were grey in colour and 2-3mm in length. A single species of parasite (Tetrastichus spp.) was found to  emerge from the gall. Pruning at 30 cm had been found to be most effective in managing the pest. Spraying of thia methoxam @ 0.008%, imidacloprid @ 0.006% and monocrotophos @ 0.005% gave effective control of the pest.
Keywords: Branch gall; mango; bioecology; management